PENGARUH PENGARUH KOMITE AUDIT, DEWAN KOMISARIS DAN DEWAN DIREKSI TERHADAP KINERJA KEUANGAN PERUSAHAAN - Susi Sih Kusumawardhany; Yunita Kurnia Shanti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
This study aims to examine the effect of the audit committee, the board of commissioners and the board of directors on the company's financial performance. This study aims to prove this influence on the company's success rate in carrying out its operational activities. The population in this study are manufacturing companies in the consumer goods sector listed on the IDX in 2017-2019. The sampling method uses purposive sampling, which is a sampling technique with certain considerations. The research sample was 23 in 3 years with a total of 69 samples. The data analysis method used classical assumption test and multiple linear regression. The results of this study indicate that the board of commissioners has a significant effect on the company's financial performance, meaning that a large size of the board of commissioners causes better management monitoring and can minimize fraud in the company so that the company's financial performance is getting better. The audit committee and the board of directors have no significant effect on the company's financial performance. This shows that the size or size of the audit committee does not guarantee the effectiveness of the audit committee's performance in supervising the company's financial performance, and the size of the board of directors does not guarantee the effectiveness of carrying out its responsibilities in managing the company. Keywords: audit committee, board of commissioners, board of directors, financial performance